Stakeholder and patient experience with virtual reality in burn treatment - a study of the Cold River application in a clinical setting - Zielina, Martin; Zajíček, Robert; Lipový, Břetislav (Acta chirurgiae plasticae, 2024)
The use of virtual reality (VR) in medicine is rapidly expanding, particularly in areas like pain management, surgical training, and mental health therapy. This study examines the implementation and effects of the Cold River VR application, a fully immersive tool designed to help manage pain and anxiety during dressing changes for burn trauma patients in a Czech hospital. The Cold River application immerses patients in a peaceful, interactive virtual environment, utilizing eye-tracking technology to engage them without the need for physical controllers, which could interfere with wound care. The study included 67 participants and found that Cold River effectively distracted patients, making the often painful and anxiety-provoking dressing changes more bearable. While stakeholder interviews indicated that the VR application was generally well-received and seen as a valuable tool in reducing patient discomfort, challenges such as lengthy calibration and occasional issues with nausea and headset discomfort were noted. Importantly, the Cold River application increased patient engagement and reduced the psychological burden associated with burn care, though it also highlighted the need for customization based on individual patient preferences and conditions. Overall, the experience with Cold River suggests that immersive VR holds significant potential for improving patient care during burn treatment, particularly when tailored to specific patient needs and contexts.
Keywords: senioři; Patients; popálení; Attitude of Health Personnel; Middle Aged; mužské pohlaví; Cold River; Adult; mladý dospělý; postoj zdravotnického personálu; Burns; Young Adult; ženské pohlaví; Humans; Pain Management; Virtual Reality Exposure Therapy; lidé středního věku; management bolesti; pacienti; terapie pomocí virtuální reality; dospělí; Female; Aged; lidé; Male